2019
DOI: 10.1111/1440-1630.12620
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of individuals receiving occupational therapy services through the National Disability Insurance Scheme: Implications for occupational therapy educators

Abstract: Introduction:With the introduction of the National Disability Insurance Scheme (NDIS) in Australia, occupational therapy graduates need to be adequately prepared to support service users in this new policy context. There is, however, limited research informed by service users themselves to inform contemporary occupational therapy curriculum redesign. The aims of this study were: (a) to explore the experience of occupational therapy service provision from the perspective of service users with lived experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“… NDIS: National Disability Insurance Scheme; NDIA: National Disability Insurance Agency; PSD: psychosocial disability. † Numbers listed in this column refer to the following publications: 1, Aitken et al (2019); 2, Barclay et al (2020); 3, Cashin (2014); 4, Dickinson and Carey (2017); 5, Diminic et al (2019); 6, Furst et al (2018); 7, Gillieatt et al (2018); 8, Hancock et al (2017); 9, Hayes et al (2018); 10, Horsfall et al (2018); 11, Isaacs et al (2018); 12, Kay and Kendall (2017); 13, Maker et al (2017); 14, Malbon et al (2019); 15, McGorry and Hamilton (2016); 16, Mellifont (2017); 17, Mulder (2017); 18, New South Wales Nurses’ Association (2019); 19, Pereira et al (2020); 20, Reppermund et al (2018); 21, Rosenberg (2017); 22, Rosenberg et al (2019); 23, Salvador-Carulla and Einfeld (2014); 24, Schweizer et al (2018); 25, Simpson et al (2016); 26, Stewart et al (2018); 27, Trollor (2014); 28, Williams and Smith (2014). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… NDIS: National Disability Insurance Scheme; NDIA: National Disability Insurance Agency; PSD: psychosocial disability. † Numbers listed in this column refer to the following publications: 1, Aitken et al (2019); 2, Barclay et al (2020); 3, Cashin (2014); 4, Dickinson and Carey (2017); 5, Diminic et al (2019); 6, Furst et al (2018); 7, Gillieatt et al (2018); 8, Hancock et al (2017); 9, Hayes et al (2018); 10, Horsfall et al (2018); 11, Isaacs et al (2018); 12, Kay and Kendall (2017); 13, Maker et al (2017); 14, Malbon et al (2019); 15, McGorry and Hamilton (2016); 16, Mellifont (2017); 17, Mulder (2017); 18, New South Wales Nurses’ Association (2019); 19, Pereira et al (2020); 20, Reppermund et al (2018); 21, Rosenberg (2017); 22, Rosenberg et al (2019); 23, Salvador-Carulla and Einfeld (2014); 24, Schweizer et al (2018); 25, Simpson et al (2016); 26, Stewart et al (2018); 27, Trollor (2014); 28, Williams and Smith (2014). …”
Section: Resultsmentioning
confidence: 99%
“…Of the eight publications focused specifically on the NDIS, only one publication (Barclay et al, 2020) explored the experiences of NDIS participants themselves and only two of these participants had a psychosocial disability. Equally, there was an absence of exploration of family member experiences or perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They compared past (localised) and the current centralised scheme, noting that the past localised scheme was more personalised and skilled compared to the NDIS, with mixed reviews as the system matured and improved. This concept was supported by Barclay et al (2020) where participants found that the NDIS planners ability to support choice and control was largely impacted by their knowledge of disability and corresponding needs. Previous literature further supports the notion that participants are more likely to feel supported when their planners demonstrated knowledge of the NDIS and offered advice about options (Collings et al, 2019).…”
Section: Discussionmentioning
confidence: 96%